Familial hypercholesterolaemia commonly presents with Achilles tenosynovitis. Issue 3 (21st September 2005) - Beeharry, D; Coupe, B; Benbow, E W; Morgan, J; Kwok, S; Charlton-Menys, V; France, M; Durrington, P N
Abstract : Background: Patients with heterozygous familial hypercholesterolaemia (HeFH) develop tendon xanthomata (TX), most commonly in their Achilles tendons. Even before tendons are chronically enlarged, tenosynovitis may occur and medical advice be sought. Untreated HeFH carries a high risk of premature coronary heart disease, which can be ameliorated by early diagnosis. Objective: To determine the prevalence of episodes of Achilles tendon pain in HeFH before its diagnosis. Methods: Patients with definite HeFH (Simon Broome criteria) attending a lipid clinic were identified. They completed a questionnaire asking about symptoms relating to their Achilles tendons. Unaffected spouses or cohabiting partners served as controls. Results: 133 patients (47% men) and 87 controls (51% men) participated. TX had been recognised by the referring physicians in <5% of cases. However, 62 (46.6% (95% confidence interval (CI) 38.1 to 55.1)) patients had experienced one or more episodes of pain in one or both Achilles tendons lasting >3 days, whereas only 6 (6.9% (1.6 to 12.2)) controls had done so (difference p<0.001; likelihood ratio 6.75). Typically, in the patients with HeFH the pain lasted 4 days (median). It was described as severe or very severe in 24/62 (38.7% (30.4 to 47.0)) patients with HeFH, but never more than moderate in controls. 35 (26.3% (18.8 to 33.8)) patients with HeFH had consulted a doctor about Achilles tendon pain, but in no case had this led to a diagnosis of HeFH. None of the controls had consulted a doctor. Conclusions: Measurement of serum cholesterol in patients presenting with painful Achilles tendon could lead to early diagnosis of HeFH.